Effects of Piper crocatum leaf extract-based ointments on bacteria associated with diabetic ulcers: an in vitro study - Nuari, Yudha Rizky; Abusri, Mila; Yuntari, Wahyu; Tryadi, Oca Maharani; Ardhiana, Fiarriescha Marra (Pharmaciana, 2024)
Diabetic patients with poor blood glucose control are highly susceptible to developing secondary infections, which can lead to the development of prolonged diabetic ulcers. Therefore, a suitable medication that may effectively prevent the occurrence of secondary infections is crucial to shorten the closure of diabetic ulcers. Red betel leaf (Piper crocatum Ruiz & Pav) reportedly possesses antimicrobial activity due to the presence of flavonoids. This study aimed to evaluate the effect of ethanolic extract of red betel leaf (EERBL) ointments against the most prevalent bacteria associated with diabetic foot ulcers (DFU): Staphylococcus aureus and Pseudomonas aeruginosa. The EERBL was prepared by macerating powdered red betel leaf with 96% ethanol and was screened for the presence of flavonoids and the determination of total flavonoid content (TFC) by thin layer chromatography and UV-Vis spectrophotometry, respectively. This study examined three hydrophilic-based ointments containing 10%, 20%, and 30% EERBL, respectively, followed by characterization for pH, spreadability, stickiness, and viscosity. The EERBL ointments' effect on the bacteria was evaluated using the well-diffusion method by observing inhibition zone formation after 24-hour incubation. The results showed that varying the EERBL concentrations in the formulations led to different spreadability, stickiness and viscosity (p<0.05). Furthermore, all EERBL ointments demonstrated the formation of an inhibition zone on cultured media, indicating the presence of antimicrobial activity. The ointment with 30% EERBL had the largest diameter of the inhibition zone against both bacteria (p<0.05). The findings suggest enhanced antimicrobial activity was observed with an increase in the concentration of EERBL within the ointments.